Pentadic analysis of environmental communication: a case study of East Kalimantan, Indonesia - Fajaria Menur Widowati; Maharina Novia Zahro (Jurnal Studi Komunikasi, 2025)
Abstract This research hoped to find out the environmental communication practices in the management of the Wehea protected forest in Nehas Liah Bing Village, East Kutai, East Kalimantan, Indonesia, through the perspective of Kenneth Burke's Dramatism. This research sought human relations in performing symbolic actions by paying attention to the sources, limits, and paradoxes of using symbols, particularly regarding motives in communication actions and revealing discourse contestation among environmental rhetorics. This research used ethnographic communication methods. The data collection was conducted by observation, in-depth interviews, and analysis of archival, textual, or visual data obtained from field research. The data was analysed using Kenneth Burke's Pentad analysis. The researchers conclude that four key actors are involved and six distinct scenes or phases in the cycle of drama related to environmental communication in Nehas Liah Bing Village. Among the four actors, three are environmental actors or rhetors, each with different motives and interests driving their involvement in establishing the Wehea protected forest. Nevertheless, they can collaborate to save the environment. This study's theoretical implication shows that dramatism as a new rhetorical theory can be used in environmental communication studies to explore the relationship between agencies, institutions, and power in certain situations or conjunctions involved in the establishment and management of Indigenous community-based protected forests.